Who Uses Right-Wing Alternative Online Media? An Exploration of Audience Characteristics - Schulze, Heidi (2020)
Accompanying the success of the radical right and right-wing populist movements, right-wing alternative online media have recently gained prominence and, to some extent, influence on public discourse and elections. The existing scholarship so far focuses primarily on the role of content and social media distribution and pays little attention to the audiences of right-wing alternative media, especially at a cross-national level and in the European context. The present paper addresses this gap by exploring the characteristics of the audiences of right-wing alternative online media. Based on a secondary data analysis of the 2019 Reuters Digital News Survey, this article presents a cross-national analysis of right-wing alternative media use in Northern and Central Europe. The results indicate a comparatively high prevalence of right-wing alternative online media in Sweden, whereas in Germany, Austria, and Finland, these news websites seem to be far less popular. With regard to audience characteristics, the strongest predictors of right-wing alternative online media use are political interest and a critical stance towards immigration, accompanied by a skeptical assessment of news quality, in general, and distrust, especially in public service broadcasting media. Additionally, the use of social media as a primary news source increases the likelihood of right-wing alternative news consumption. This corroborates the high relevance of social media platforms as distributors and multipliers of right-wing alternative news content. The findings suggest that right-wing alternative online media should not be underestimated as a peripheral phenomenon, but rather have to be considered influential factors for center-right to radical right-leaning politics and audiences in public discourse, with a high mobilizing and polarizing potential.